Human dihydroorotate dehydrogenase inhibitors, a novel approach for the treatment of autoimmune and inflammatory diseases - Leban, Johann; Vitt, Daniel (Arzneimittelforschung, 2011)
Dihydroorotate dehydrogenase (DHODH), a novel and recently discovered enzyme, is involved in the biosynthesis of uridine. Leflunomide (CAS 75706-12-6), a drug approved for the treatment of treat rheumatoid arthritis (RA), was identified as an inhibitor of DHODH.Structure based drug design using the leflunomide/DHODH X-ray structure yielded novel inhibitors with improved pharmacological properties. Such drug candidates are in clinical trials against various autoimmune diseases.
Keywords: CAS 75706-12-6; Dihydroorotate dehydrogenase inhibitors; Disease modifying antirheumatic drug; Leflunomide; X-ray structure based drug design